Implementation of Hospital Occupational Health and Safety Standards at General Hospitals in Kendari City - Damayanty, Sri; Susanto, Agus; Hipta, Wahyu Fajriana (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
A hospital is a health service facility with various activities with many potential dangers for hospital human resources and patients or patient companions. Potential hazards in the hospital can be in the form of occupational diseases and infectious diseases. There are also other potential hazards that affect the situation and conditions in the hospital. The specific objective of this research is to see the implementation of the Occupational Health and Safety standards, implemented in 3 (three) General Hospitals in Kendari City, Southeast Sulawesi. This research uses qualitative research methods with an observational approach and in-depth interviews. This research took place in 3 (three) General Hospitals in Kendari City, namely: Hospital A, Hospital B, and Hospital C. The informants in this study are those related to the K3 standard policies implementation in hospitals. The results showed that there are several hospitals that have not carried out all the stages of equipped facilities and infrastructure related to risk management aspects, efforts to manage hazardous and toxic materials (B3) from occupational safety and health aspects, to prevent and control fire as well as efforts to prepare for the face. Emergency or Disaster Conditions. It shows that the K3RS standards implementation in several hospitals has not been implemented optimally. It is recommended for the hospital to continue to refer to the rules governing the K3RS implementation. It includes the lack of infrastructure and facilities. Like always, briefings for all officers before working and evaluation at the end of each working hour.